The New Life: Construction sites and mine fields - Women and Victims of Trafficking, FIZ Advocacy and Support for Migrant (Anti-Trafficking Review, 2018)
Interview with Sara Donath, counsellor at FIZ Fachstelle Frauenhandel und Frauenmigration (FIZ – Advocacy and Support for Migrant Women and Victims of Trafficking, Switzerland). Sara Donath has counselled hundreds of survivors of trafficking and accompanied them into their new lives. We asked Sara about the experiences of these women after having experienced exploitation and violence.